Monitoring Spatial Distribution of Nonpathogenic Fusarium Oxysporum in the Rhizosphere and Roots of Banana Using Β-D-Glucuronidase and Green Fluorescent Protein - Wong , Pui See (2005)
This study was conducted to monitor the spatial distribution of nonpathogenic isolate of Fusarium oxysporum (Fo4), using a detectable marker. Fo4 was transformed by GUS gene fusion system (Escherichia coli β-D-glucuronidase gene) and GFP (Green Fluorescent Proteins). The GUS was detected by 5-bromo-4-chloro-3-indolyl-β-D-glucuronide (X-Gluc). The GFP activity was detected under a fluorescence microscope. There was no different in the cultural and morphological characteristics between the transformed and non-transformed Fo4. The antagonistic activity against Fusarium oxysporum f. sp. cubense Race 4 (FocR4) was maintained at values within the range of 56.98–41.56% based on the Percentage Inhibition of Radial Growth (PIRG) in vitro. DNA polymorphism (RAPD) screening by the primers OPC-15 and OPC-11, confirmed that no mutation had occurred after the transformation and, band GUS-F vs. GUS-R and 5-GFP vs. 3-GFP showed that transformed Fo4 still carried the GUS and GFP gene after five consecutive conidiation/ generation cycles in culture. The frequency of re-isolation on PCNB medium amended with 40 µg/ml X-Gluc and 200 µg/ml hygromycin B was highest (45.48 x 103 cfu/g roots) in the rhizosphere of banana plantlet at day 24, and remained to stabilize at between 37.24 x 103 cfu/g roots to 34.52 x 103 cfu/g roots until the end of sampling at day 36. The transformed Fo4 can be detected inside the root tissues even 4 days after inoculation although the colony forming units (cfu) (1 cfu/g roots) was substantially lower than that detected on the root surface (11.76 x103 cfu/g roots), suggesting that they were colonizing the root and living on the root exudates. The population of transformed Fo4 in the non-rhizosphere soil initially fell sharply with the time of sampling, but thereafter remained stable (4.38-18.00 x 104 cfu/g soil) until 36 days of sampling.